The association between VEGF genetic variations and the risk of bronchopulmonary dysplasia in premature infants: a meta-analysis and systematic review - Golshan-Tafti, Mohammad; Bahrami, Reza; Dastgheib, Seyed Alireza; Hosein Lookzadeh, Mohamad; Mirjalili, Seyed Reza; Yeganegi, Maryam; Aghasipour, Maryam; Shiri, Amirmasoud; Masoudi, Ali; Shahbazi, Amirhossein; Azizi, Sepideh; Noorishadkam, Mahmood; et al. (Frontiers in Pediatrics, 2024)
Objective: Previous studies on the link between VEGF gene polymorphisms and bronchopulmonary dysplasia (BPD) have yielded inconsistent results. This meta-analysis sought to clarify the relationship between genetic variations in the VEGF gene and the risk of BPD. Methods: Data were collected from multiple databases, including PubMed, Scopus, EMBASE, and CNKI, up to January 5, 2024. Results: Nineteen case-control studies were analyzed, featuring 1,051 BPD cases and 1,726 healthy neonates. The analysis included four studies on the -460T/C polymorphism (312 cases, 536 controls), four on the -2578C/A polymorphism (155 cases, 279 controls), six on the +405G/C polymorphism (329 cases, 385 controls), and five on the +936C/T polymorphism (225 cases, 526 controls). The meta-analysis suggests that the -460T/C polymorphism may protect against BPD (C vs. T: OR=0.715, 95% CI 0.543-0.941, p=0.017; CC vs. TT: OR=0.478, 95% CI 0.233-0.983, p=0.045; CC vs. CT+TT: OR=0.435, 95% CI 0.248-0.764, p=0.004). No significant associations were found between the -2578C/A, +405G/C, and +936C/T polymorphisms and BPD susceptibility. Conclusions: This meta-analysis indicates that the C allele of the -460T/C polymorphism may offer protection against BPD. No significant associations were observed for the -2578C/A, +405G/C, and +936C/T polymorphisms.